2021
DOI: 10.3390/medicina57040338
|View full text |Cite
|
Sign up to set email alerts
|

Medial Calcar Comminution and Intramedullary Nail Failure in Unstable Geriatric Trochanteric Hip Fractures

Abstract: Background and Objectives: An increasing global burden of geriatric hip fractures is anticipated. The appropriate treatment for fractures is of ongoing interest and becoming more relevant with an aging population and finite health resources. Trochanteric fractures constitute approximately half of all hip fractures with the medial calcar critical to fracture stability. In the management of unstable trochanteric fractures, it is assumed that intramedullary nails and longer implants will lead to less failure. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
1
0
Order By: Relevance
“…Because the definition of the stability of trochanteric fractures is still controversial, it is the possible cause of the complication of the choice of osteosynthesis [8], especially in the elderly; for that reason, continues to be a tremendous public health problem in terms of patient mortality, morbidity, and burden to the healthcare system. We agree that the definitions of unstable fractures vary but include those with a fractured lesser trochanter, reverse fracture line, or intertrochanteric comminution associated with a big posteromedial component, a broken greater trochanter, and lateral cortex breach [9].…”
mentioning
confidence: 93%
“…Because the definition of the stability of trochanteric fractures is still controversial, it is the possible cause of the complication of the choice of osteosynthesis [8], especially in the elderly; for that reason, continues to be a tremendous public health problem in terms of patient mortality, morbidity, and burden to the healthcare system. We agree that the definitions of unstable fractures vary but include those with a fractured lesser trochanter, reverse fracture line, or intertrochanteric comminution associated with a big posteromedial component, a broken greater trochanter, and lateral cortex breach [9].…”
mentioning
confidence: 93%
“…Applying PFNA xation alone on patients is prone to complications such as coxa vara, internal xation loosening and cutting out, resulting in internal xation failure. [9,10] Clinically, some scholars attempted to achieve early stability by reconstructing the lateral femoral wall with locking plate, improving the mechanical conduction at proximal femoral and increasing the balance and stability of the soft tissues of hip joint. Through the comparison between the effects of locking plate reconstruction of the lateral wall and PFNA internal xation, the former method proves to have obvious advantages in the aspects of fracture healing time, weight-bearing exercise time and improvement of hip joint function.…”
Section: Introductionmentioning
confidence: 99%
“…The calcar femorale, or medial calcar, plays a critical role in managing the compressive loads on the femoral head and effectively redistributing such forces through the diaphysis. In addition, the medial calcar has been identified as essential in determining intertrochanteric (IT) fracture stability [ 1 ]. Recent trends have shown that IT fractures are most commonly managed with intramedullary nailing [ 2 ].…”
Section: Introductionmentioning
confidence: 99%